2007
DOI: 10.2193/2006-352
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Missouri Small Game Hunters Toward Nontoxic‐Shot Regulations

Abstract: Wildlife managers are becoming more concerned about the exposure of birds, in addition to waterfowl, to spent lead shot. Knowledge of hunter attitudes and their acceptance of nontoxic‐shot regulations will be important in establishing new regulations. Our objective was to assess the attitudes of small game hunters in Missouri, USA, toward a nontoxic‐shot regulation for small game hunting, specifically for mourning doves (Zenaida macroura). Most hunters (71.7–84.8%) opposed additional nontoxic‐shot regulations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Given the range of these data, it appears that hunters may be poisoning a significant number of mourning doves with lead pellets each year. Available information indicates that most dove hunters would not favor additional lead shot restrictions for dove hunting (Levengood et al 1999, Schulz et al 2006b). We contend the continued use of lead shot may be indefensible from an increased crippling rate argument.…”
Section: Nontoxic Shot and Increased Crippling?mentioning
confidence: 99%
“…Given the range of these data, it appears that hunters may be poisoning a significant number of mourning doves with lead pellets each year. Available information indicates that most dove hunters would not favor additional lead shot restrictions for dove hunting (Levengood et al 1999, Schulz et al 2006b). We contend the continued use of lead shot may be indefensible from an increased crippling rate argument.…”
Section: Nontoxic Shot and Increased Crippling?mentioning
confidence: 99%
“…Despite this information, approximately 50–53% of Illinois, USA, mourning dove hunters opposed a nontoxic‐shot regulation for dove hunting (Anderson and David , Levengood et al , Miller et al ). Similarly, other surveys of dove hunters showed hunters having little awareness of the problem and little desire to change behavior (Case and Associates , ; Schulz et al ). Small‐game hunters in Minnesota, including dove hunters, had little awareness of lead poisoning in mourning doves, but reported they would be receptive to nonlead ammunition messages from hunter organizations like Ducks Unlimited (Schroeder et al ).…”
Section: Need For a More Strategic Approachmentioning
confidence: 88%
“…Few human‐dimensions research studies have documented hunters’ attitudes toward nonlead ammunition (Schulz et al ), behavioral mechanisms affecting hunters’ voluntarily use of nonlead ammunition (Schroeder et al ), or existing voluntary programs (Bedrosian et al , Chase and Rabe ). As mentioned earlier, research has shown mourning doves succumb to lead poisoning (Schulz et al , , , ).…”
Section: Need For a More Strategic Approachmentioning
confidence: 99%
“…We still lack knowledge of the impacts of using a lottery system on an area's dove harvest. Similarly, given the attitudes of hunters to nontoxic‐shot restrictions (Schulz et al 2007 b ), there is a need to confirm whether public areas will see decreases in hunting and numbers of doves harvested if shot‐type restrictions are used.…”
Section: Discussionmentioning
confidence: 99%